Examinando la prominente posición de Chile a nivel mundial en cuanto a desigualdad de ingresos: Comparaciones regionales - Juan Pablo Valenzuela; Suzanne Duryea (Estudios de Economía, 2011)
– In the Latin American context, Chile has the highest level of per capita income and the human development index, though the distribution of income is quite unequal. Unlike Uruguay, Chile has one of the more unequal income distributions of the region. In 2003, Chile had Gini Coefficient of 8.5 points higher than Uruguay. Using micro/simulations, the analysis shows that most of the difference regarding income distribution comes from the wealthier households, particularly those that belong to the top 2%. Those households get the greatest proportion of resources coming from non-labor income. At the same time, the difference in returns to higher education explains another 20% of the income differences between Chile and Uruguay. Social conditions such as social security benefits and the participation of women in the labor market are not significant to explain the differences between these countries. Finally, this paper shows that national account adjustment to income information in Chilean households survey explains a third of the Gini coefficient gap between Chile and Uruguay, without the national account adjustment, the income distribution gap among both countries would diminish in three points from earlier estimation. Even though this significative reduction the reasons to explain the gap would remain identical than previous analysis.
Keywords: D3; J2; J3; 330; microsimulation; income distribution; inequality; pensions; labor participation; returns to schooling; Einkommensverteilung; Disparitätsmaß; Regionale Einkommensverteilung; Mikrosimulation; Chile; Uruguay